Ð’Ð»Ð¸ÑÐ½Ð¸Ðµ ÐºÑÐµÐ½Ð¾Ñ‚Ñ€Ð°Ð½ÑÐ¿Ð»Ð°Ð½Ñ‚Ð°Ñ†Ð¸Ð¸ ÐºÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð½Ð¾Ð¹ Ð¾Ñ€Ð³Ð°Ð½Ð½Ð¾Ð¹ ÐºÑƒÐ»ÑŒÑ‚ÑƒÑ€Ñ‹ Ñ‰Ð¸Ñ‚Ð¾Ð²Ð¸Ð´Ð½Ð¾Ð¹ Ð¶ÐµÐ»ÐµÐ·Ñ‹ Ð½Ð° Ñ„Ð¸Ð·Ð¸Ð¾Ð»Ð¾Ð³Ð¸Ñ‡ÐµÑÐºÐ¸Ðµ Ð¿Ð°Ñ€Ð°Ð¼ÐµÑ‚Ñ€Ñ‹ ÑÐºÑÐ¿ÐµÑ€Ð¸Ð¼ÐµÐ½Ñ‚Ð°Ð»ÑŒÐ½Ñ‹Ñ… Ð¶Ð¸Ð²Ð¾Ñ‚Ð½Ñ‹Ñ… - Volkova, N. A.; Bozhok, G. A.; Alabedalkarim N.M., N.M. Alabedalkarim N.M.; Legach, Ye. I.; Bondarenko, T. P. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2003)
The functioning of native and cryopreserved organ culture of thyroid gland (OCThG) of newborn piglets at various terms after xenotransplantation in an organism of experimental animals was studied. It was shown that OCThG subjected to low temperature storage after xenotransplantation is able to synthesize and secrete thyroid hormons. It was established, that xenotransplantation of native, cryopreserved and recultured OCThG led to the increase of T3,T4 in blood plasma level in the rabbits with experimental hypothyrosis.